“INTEGRASI ISLAM DAN SAINS DALAM PENGEMBANGAN KURIKULUM DI UIN (Evaluasi Penerapan Integrasi Islam dan Sains di UIN dalam Kurikulum dan Proses Pembelajaran)” - Wismanto; Munzir Hitami; Abu Anwar (JURNAL RANDAI, 2021)
“This research is based on the reasoning that transformation of IAIN to UIN can not release the expectation to do the integration of science and shake off dichotomy both Islam and science. The dichotomous of Islam and science appear in cosequence of the differences at the level of ontological, epistemological and axiological in religious sciences (Islam) and general sciences. In response to preliminary research and findings with respect to science integration in UIN, researchers assume to do comprehensive research to find out at analyzing the implementation of the integration of science in UIN throughout Indonesia, especially in the context of curriculum design and the learning process